2023
DOI: 10.1177/20438087231204166
|View full text |Cite
|
Sign up to set email alerts
|

Value-modulated attentional capture in reward and punishment contexts, attentional control, and their relationship with psychopathology

René Freichel,
Lana Mrkonja,
Peter J. de Jong
et al.

Abstract: Attentional bias towards rewards has been extensively studied in both healthy and clinical populations. Several studies have shown an association between reward value-modulated attentional capture (VMAC) and greater substance use. However, less is known about the association between these VMAC effects and internalizing symptoms. Moreover, while VMAC effects have also been found in punishment contexts, the association between punishment VMAC and psychopathology has not been studied so far. In the present two-pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Using the probability of fixating the distractor, reliable learning-dependent reductions in distractor processing can be observed (Grégoire et al, 2022; Kim & Anderson, 2022), in addition to a measure of attention capture that is reliable for both young and older adults regardless of whether capture is overall suppressed under conditions of feature-search vs. singleton-search. Even when accounting for the increased variance in difference score calculations (Miller & Ulrich, 2013; Paap & Sawi, 2016; Weichselbaum et al, 2018), we demonstrate that oculomotor measures of attention capture on average exhibit strong reliability (mean across acquired values, r = .735) and are considerably more reliable than response time-based measures (Anderson & Kim, 2019; Freichel et al, 2023; Garre-Frutos et al, 2024; Ivanov et al, 2023).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Using the probability of fixating the distractor, reliable learning-dependent reductions in distractor processing can be observed (Grégoire et al, 2022; Kim & Anderson, 2022), in addition to a measure of attention capture that is reliable for both young and older adults regardless of whether capture is overall suppressed under conditions of feature-search vs. singleton-search. Even when accounting for the increased variance in difference score calculations (Miller & Ulrich, 2013; Paap & Sawi, 2016; Weichselbaum et al, 2018), we demonstrate that oculomotor measures of attention capture on average exhibit strong reliability (mean across acquired values, r = .735) and are considerably more reliable than response time-based measures (Anderson & Kim, 2019; Freichel et al, 2023; Garre-Frutos et al, 2024; Ivanov et al, 2023).…”
Section: Discussionmentioning
confidence: 73%
“…Over the three measures, the authors report poor to moderate split-half reliability over response times and poor reliability over accuracy, in addition to poor test-retest reliability with respect to both response times and accuracy. Furthermore, three studies investigating selection history effects of reward learning in visual search also reported poor test-retest reliability of behavioral response times (Anderson & Kim, 2019; Freichel et al, 2023; Garre-Frutos et al, 2024). These studies collectively identified that response time exhibits poor reliability over experience-driven attention effects.…”
Section: Introductionmentioning
confidence: 99%